An International Sensitivity Index (ISI) derived from patients with abnormal liver function improves agreement between INRs determined with different reagents - Sermon, Anne M.; Smith, Julie M.; Maclean, Rhona; Kitchen, Steve (Thrombosis and Haemostasis, 2010)
The International Normalised Ratio (INR)/International Sensitivity Index (ISI) system was developed as a way to standardise the prothrombin time during the monitoring of patients undergoing oral anti-coagulant therapy with vitamin K antagonists. The wide acceptance of the INR has led to its use as one of three parameters used in the Model for End stage Liver disease (MELD) scoring system to aid the prioritisation of patients for liver transplant. Literature published recently has highlighted the potential inadequacy of the INR system in this context. Our aim was to investigate the degree of difference between INR values calculated using an ISI derived from warfarinised patients and those calculated using an ISI derived from patients with liver disease. Prothrombin times from 60 patients with liver disease were determined using three working thromboplastin reagents; Innovin®, Thromborel S® and Thromboplastin C® and two reference thromboplastins; rTF/95 and RBT/05. All thromboplastin reagents tested had standard international sensitivity indices (ISIs) assigned following calibration with patients on oral anticoagulant therapy (ISIvka). As a result of the new calibration each of the working thromboplastin reagents was assigned a specific “liver patient” ISI. Two INR values were calculated for each thromboplastin patient involved in the calibration. A comparison of the mean INRliver with INRvka showed a statistically significant difference between the two values (p<0.0001). A similar relationship existed for INRs on a further 20 patients with liver disease whose plasmas were not used to derive the ISIliver. This difference led to a change in the final MELD score and could therefore affect the prioritisation and management of these patients.
Keywords: Liver disease; international normalised ratio; standardisation